Menuju Pembangunan Berkelanjutan dan Inklusif dalam Kolaborasi antara Pemerintah, Swasta dan Masyarakat Sipil - Shabrina Aribby Leone; Bagas Eka Maulana; sulistya ningsih (Universitas Negeri Semarang, 2025)
Sustainable and inclusive development has become a key global agenda that requires cross-sectoral solutions to address complex social, economic and environmental challenges. The objective of this study is to analyse the role of trisectoral collaboration between the government, private sector and civil society in promoting sustainable and inclusive development in Indonesia. The method used is a literature study with a descriptive qualitative approach, which examines various sources of literature, policy reports, and case studies. The results of the study show that collaboration between the three pillars is very effective because it can increase the effectiveness of development implementation, overcome socio-economic inequalities, and strengthen development governance. However, the dynamics of collaboration still face a number of obstacles, such as overlapping regulations, complex bureaucracy, and low levels of trust between parties. On the other hand, driving factors such as fiscal incentives, digital platforms, and political support can also strengthen this synergy. The conclusion of this study is that trisector collaboration is not only a necessity but also a strategic foundation for achieving sustainable, inclusive, and equitable development goals in Indonesia. To that end, it is imperative to simplify regulations, increase transparency, and strengthen institutional capacity.